Then sings my soul. Book 3 - Morgan, Robert J., 1952- (Nashville : Thomas Nelson, 2011)
In 2003, Robert Morgan released what would become a future classic for over a million readers, a unique book entitled Then Sings My Soul. This collection of the world's greatest hymns and the stories behind them stirred an entire generation to better understand the heritage of our faith through song. Now, in the long-awaited third volume of this series, Morgan expands his material to include the great history of worship, the first biblical hymns, biographical sketches of the most interesting composers, and almost 60 generations of hymn singing. The new book also includes a collection of the greatest hymns you've never heard, with lead-sheets included. --Publisher.
"The story of our songs: drawing strength from our great hymns of our faith"--Cover.
Includes bibliographical references and indexes.
Keywords: Hymns -- History and criticism